Inflation Expectations: Does the Market Beat Professional Forecasts? - Makram El-Shagi (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2009)
The present paper compares expected inflation to (econometric) inflation forecasts based on a number of forecasting techniques from the literature using a panel of ten industrialized countries during the period of 1988 to 2007. To capture expected inflation we develop a recursive filtering algorithm which extracts unexpected inflation from real interest rate data, even in the presence of diverse risks and a potential Mundell-Tobin-effect. The extracted unexpected inflation is compared to the forecasting errors of ten econometric forecasts. Beside the standard AR(p) and ARMA(1,1) models, which are known to perform best on average, we also employ several Phillips curve based approaches, VAR, dynamic factor models and two simple model avering approaches. – – Das vorliegende Papier vergleicht die auf dem Markt offenbarte Inflationserwartung mit den Inflationsprognosen auf der Grundlage aktueller Schätz- bzw. Prognoseverfahren für ein Panel von zehn Industriestaaten seit 1980. Zu diesem Zweck entwickeln wir ein rekursives Filterverfahren, mit dessen Hilfe aus den Realzinsdivergenzen zwischen den Industriestaaten die unerwartete Inflation geschätzt werden kann. Die verwendeten Inflationsschätzungen, mit denen die extrahierten Erwartungen verglichen werden, umfassen ARMA-Modelle, VAR-Modelle unter Berücksichtigung von konstanten oder sich im Zeitablauf verändernden Phillipskurvenffekten, VAR-Modelle, dynamische Faktorenmodelle sowie auf diesen Schätzungen basierende Modellselektion- bzw. Modelaveraging-Prognosen.
urn:nbn:de:101:1-200911033212
Keywords: E31; E37; 330; Inflation Expectations; Rational Expectations; Inflation Forecasting; Inflationserwartungen; Rationale Erwartungen; Inflationsprognosen; Inflationserwartung; Rationale Erwartung; Inflation; Prognose; Vergleich; Schätzung; OECD-Staaten